Application of the Induced Membrane in the Acute Setting of Bone Loss. Issue 1 (March 2016) - Obert, Laurent; Rondot, Thomas; Cheval, Damien; Morris, Vivien; Sergent, Pauline; Leclerc, Gregoire; Pauchot, Julien; Garbuio, Patrick; Loisel, Francois
Abstract : A prospective continuous study is reported concerning 9 cases of traumatic bone defect that were treated by the induced membrane technique in emergency. This technique involves stable fixation, flap if necessary, and filling the void created by the bone defect by a cement spacer [poly(methyl methacrylate) without antibiotic]. This technique needs a second-stage procedure where the cement is removed and the void is filled by cancellous bone. The key point is to respect the foreign-body membrane that develops around the cement spacer, creating a biologic chamber after the second stage. Bone union was evaluated prospectively by x-ray and computed tomographic scan and was achieved with a delay of 10 months (7 to 14). Three cases needed reoperation. No septic complications occurred. Masquelet first reported 35 cases of large-bone defect of tibia nonunion treated by this technique. Flamans reported the use of the technique at hand level in emergency. Work on animal models reported by Pelissier and Viateau showed the properties of the membrane: secretion of growth factors and osteoinductive activity of the cells. Giannoudis reported the same results in human induced membrane. This technique is reliable to avoid graft and microsurgery in emergency.